Pemberdayaan terhadap Usaha Produktif Umkm melalui Pendekatan Digital Marketing di Desa Ledokombo Kabupaten Jember - Supriono, Agus; Riza Oktafiyani; Rachmat Udhi Prabowo; Julian Adam Ridjal; Ebban Bagus Kuntadi (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2024)
Ledokombo Village is one of the villages in the eastern part of Jember Regency, East Java Province. This village is within the administrative area of Ledokombo District. The area of Ledokombo Village is bordered by the areas of neighboring villages, such as Sukogidri Village, Ledokombo District, and Cumedak Village, Sumberjambe District. One of the elements of society that drives the economy is MSMEs in Ledokombo Village. The MSME players in Ledokombo Village are the "Banana Chips" MSME, which is committed to having a productive business but does not yet have a business network and knowledge about optimizing product marketing and has experienced a decline in orders from consumers. This is because the product marketing system is still conventional. The location of the service was Ledokombo Village, Jember Regency. The method of implementing the service uses the survey, FGD, socialization, training, and mentoring methods for Banana Chips MSMEs. Therefore, it is necessary to carry out appropriate empowerment efforts through counseling and training in optimizing business by utilizing marketplaces and social media. The results of the service show that the program that has been implemented has been well adopted by the Banana Chips MSMEs in Ledokombo Village. This is demonstrated by the packaging of products sold to consumers using packaging that has been recommended by the service implementation team. Improved service to consumers is based on innovative, creative principles and what is needed by the market.